Silicon biostimulant enhances the growth characteristics and fortifies the bioactive compounds in common and Tartary buckwheat plant - Azad, Md Obyedul Kalam; Park, Beom Sun; Adnan, Md; Germ, Mateja; Kreft, Ivan; Woo, Sun Hee; Park, Cheol Ho (Journal of Crop Science and Biotechnology, 2021)
Silicon is a potential biostimulant that has been used to enhance the yield and quality of plant products. Therefore, we aimed to evaluate the effect of soluble silicon on the growth characteristics and bioactive compounds content of common and Tartary buckwheat. The silicon was applied with three different doses such as low, medium, and high three times after 3 weeks of buckwheat sowing at 10 days interval. The control was done without the application of silicon. It is observed that silicon has a significant influence on having identical inclination on growth and bioactive compounds accumulation in both buckwheat cultivars. Our study showed an interesting result that lower doses of silicon enhance the growth characteristics, total and single phenolic substances (syringic acid, 4 hydroxy benzoic acid, ferulic acid), total flavonoids, rutin, quercetin content, and antioxidant capacity in common buckwheat, on the other hand, higher doses of silicon favor for Tartary buckwheat. Moreover, further investigation is needed to evaluate the optimal dose and mode of action of silicon for the enhancement of growth and phytochemical content in buckwheat plants.